The Need to Unify the Text of the Instruction on the Medical Use of Vaccines - N. A. Ozeretskovskiy (Эпидемиология и вакцинопрофилактика)
The article analyzes the content of instructions for use of vaccines and toxoids registered in the Russian Federation. It was stated that this important document is a standard of the manufacturer, and not a standard of the Ministry of Health of Russia, and does not always correspond to other regulatory documents. It is noted that instructions for foreign immunobiological preparations often differ significantly from instructions for similar domestic preparations. Examples of foreign vaccine instructions are given, the text of which does not match Russian requirements, in addition, they contain recommendations and information contradicting the Order of the Ministry of Health of Russia dated September 21, 2016 No. 724n «On approval of the Requirement for instructions on the medical use of drugs». There were suggestions to discuss the issue of unifying the text of instructions on immunobiological preparations and assigning them the title of a legal document.